Deep Vein Thrombosis associated with Cesarean Delivery: An Overview Illustrative Study (Advances in Applied Biological Research, 2025)
The risk of deep vein thrombosis (DVT) in women is strongly associated with  pregnancy, the risk increasing by 5 to 10 times. This risk then gradually increases  until it peaks during and after delivery. Blood clots are one of the most feared  complications after childbirth. They usually occur in the legs or pelvis and can  dislodge and travel to the lungs, causing pulmonary embolism. It can be controlled  on this state by using blood-thinning medications to avoid death. This problem  occurs as one complication of a cesarean section, which involves a surgical  technique for delivering a baby through an incision in the abdomen and uterus.  It is performed as an alternative to vaginal delivery. Although the risk of venous  thromboembolism increases with surgical delivery, there is no consensus on the  prevention of clots after cesarean section.
Keywords: Deepvein; Thrombosis; Cesarean Delivery; illustrative study